Ethnic disparities in out-of-pocket expense on medicines in Peru: Evidence from a nationwide survey - Jerry K. Benites-Meza; Liseth Pinedo-Castillo; Miguel Cabanillas-Lazo; Percy Herrera-Añazco; Benoit Mougenot; Vicente A. Benites-Zapata (Elsevier, 2023)
Background: Despite improvements in health insurance coverage, out-of-pocket (OOP) health spending remains a public health issue in Peru, and OOP payment has implications for disease treatment in ethnic minorities. We aimed to analyze the ethnic disparities in the OOP payment and estimate the gaps related to observable risk factors in the OOP payment on medicines by ethnic conditions during 2014-2016 in Peru. Study design: cross-sectional study. Methods: We conducted a secondary data analysis using the National Health User Satisfaction Survey. The outcome was the participants' OOP payment in self-reported medications. Ethnic minorities were considered participants who habitually spoke a language other than Spanish at home. Crude and adjusted linear regression models were performed, and the Oaxaca-Blinder decomposition method was used to assess the OPP payment differential by ethnic minority condition, explained by their individual and sociodemographic characteristics. Results: We analyzed 11,346 surveyed, the mean age was 40.78 years, and 57.67 % were women. There was lower OOP payment in medications among ethnic minorities in the adjusted analysis (Beta coefficient [β]: −0.11; 95 % confidence interval [95%CI]: −0.21 to −0.01; p = 0.043). In the Oaxaca-Blinder decomposition analysis, a gap of 0.19 USD in the OOP payment in medicines among ethnic minorities was found (p < 0.001), and the explained component by the variables measured in this research only represents 40.5 % of the gap (p = 0.001). Conclusion: There was less OOP expenditure on medicines in ethnic minorities. However, the measured variables explain only 40.5 % of these gaps. Therefore, we recommend future research that measures other variables that explain aspects of OOP spending on medicines not identified in this research. Likewise, our findings can be used to establish policies with an intercultural approach that adapt health documents to native languages or are disseminated by trained people from their communities.